Updated determination of D0-D [bar] 0 mixing and CP violation parameters with D0→K+π- decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2018)
We report measurements of charm-mixing parameters based on the decay-time-dependent ratio of D0→K+π− to D0→K−π+ rates. The analysis uses a data sample of proton-proton collisions corresponding to an integrated luminosity of 5.0 fb−1 recorded by the LHCb experiment from 2011 through 2016. Assuming charge-parity (CP) symmetry, the mixing parameters are determined to be x'2=(3.9±2.7)×10−5, y′=(5.28±0.52)×10−3, and RD=(3.454±0.031)×10−3. Without this assumption, the measurement is performed separately for D0 and ¯D0 mesons, yielding a direct CP-violating asymmetry AD=(−0.1±9.1)×10−3, and magnitude of the ratio of mixing parameters 1.00<|q/p|<1.35 at the 68.3% confidence level. All results include statistical and systematic uncertainties and improve significantly upon previous single-measurement determinations. No evidence for CP violation in charm mixing is observed.